2019
DOI: 10.1088/1361-6463/ab4141
|View full text |Cite
|
Sign up to set email alerts
|

Lattice invisibility effect based on transverse Kerker scattering in 1D metalattices

Abstract: The present work proposes a novel method to achieve free phase propagation with unitary transmission efficiency, termed as lattice invisibility effects, based on transverse scattering in 1D cylindrical metalattices. Firstly, we extend Kerker conditions parity symmetry of electromagnetic modes, and a conciser scheme to eliminate both forward and backward scattering simultaneously is presented. Compared to sphere-like particles where the first four Mie modes are required, we find that transverse scattering can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…As expected at K1 833 nm, the incident wave propagates along the z direction and transmits through the metasurface almost without perturbation. The metasurface is rendered invisible, so-called lattice invisibility [25]. At K2 867 nm, as expected, the incident wave, expressed as the absolute value of the amplitude ratio, |E x /E 0 |, is reflected back and the metasurface behaves as a perfect mirror.…”
Section: Metasurface Invisibility For Light At Normal Incidencesupporting
confidence: 56%
See 2 more Smart Citations
“…As expected at K1 833 nm, the incident wave propagates along the z direction and transmits through the metasurface almost without perturbation. The metasurface is rendered invisible, so-called lattice invisibility [25]. At K2 867 nm, as expected, the incident wave, expressed as the absolute value of the amplitude ratio, |E x /E 0 |, is reflected back and the metasurface behaves as a perfect mirror.…”
Section: Metasurface Invisibility For Light At Normal Incidencesupporting
confidence: 56%
“…It could also be theoretically realized by the interplay of MD and EQ, which has been proposed in Ref. [25] and shown in a proof-ofconcept demonstration using core-shell SiO2@InSb and Si@InSb in a 1D metalattice geometry in the Terahertz range. Our proposed method enables the realization of metasurface invisibility in a facile extremely-thin Silicon (Si) square nanoplate metasurface, which is more practically feasible and offers technically easier integration into devices than core shell-type structures.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Asymmetric scattering manipulation due to the ED and MD interference has been studied for almost 40 years [10]. Due to the inherent phase symmetry properties of MD and MQ modes in the forward and backward directions, where the MD displays odd phase symmetry and the MQ displays an even phase symmetry [15][19], the realization of dominant TED and MQ interference in this Letter paves the way towards symmetric scattering manipulation by employing only TED and MQ, such as the unusual transverse scattering, which simultaneously displays zero forward and zero backward scattering for the nanoresonator embedded in an isotropic medium [14]. Additionally, our study clearly demonstrated that the substrate effect is nontrivial in reshaping the farfield radiation pattern and must be taken into account for scattering pattern manipulation.…”
Section: Mpmentioning
confidence: 99%
“…Additionally, a dielectric metasurface, or an array of dielectric nanoresonators, sustains overlapping resonant multipolar resonances [7][8][9]. The interplay of multipolar resonances in a metasurface or a single nanoresonator provides another degree of freedom for light tailoring, such as the Kerker effect, the anti-Kerker effect [10][11][12], and transverse Kerker scattering [13][14][15]. Kerker-type scattering, or highly suppressed backward scattering, attracts much interest as it enables a concentrated electric field inside the dielectric structure and far-field scattering in the forward direction.…”
Section: Introductionmentioning
confidence: 99%